Language and Ethnic Boundary among Students of Various Ethnicities in Secondary Schools in Malaysia - Yusof, Najeemah Mohd (SOSIOHUMANIKA, 2011)
ABSTRACT: Social interaction is a vital aspect in the creation of an identity, especially in a plural society like the one we have here in Malaysia. This study is carried out to identify the pattern of social interaction among students of various ethnicities in National Secondary Schools in Malaysia. The study sample consists of 720 students from form 1, 2, and 4. A questionnaire containing items of language and ethnic boundary was applied in order to obtain the data. The study finding shows that there is a significant difference in the mean score for every variable for students of various ethnicities. Students from National Chinese Type Schools who attend for National Secondary Schools are the one who use the least amount the âBahasa Melayuâ (Malay language) and students for National Tamil Type Schools are the one facing most of the stereotypes. Based on the study findings, a few recommendations were made regarding the social interaction among students of various ethnicities in National Secondary Schools in Malaysia. The success of increasing the social interaction pattern among students of various ethnicities depends on the policies and programs that were introduced by various agencies of the government. If it is not carried out successfully, âSatu Negara Satu Bangsaâ (One State One Nation) will only remain as a slogan without any true meaning. Key words: Students, âBahasa Melayuâ (Malay language), ethnic boundary, various ethnicities, and national integration in Malaysia.Â About the Author: Najeemah Mohd Yusof, Ph.D. is a Senior Lecturer at the School of Educational Studies USM (Science University of Malaysia), Minden 1800, Pulau Pinang, Malaysia. She can be reached at: najineen@usm.myHow to cite this article? Yusof, Najeemah Mohd. (2011). âLanguage and Ethnic Boundary among Students of Various Ethnicities in Secondary Schools in Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.4, No.2 [November], pp.211-228. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 24, 2011); Revised (October 26, 2011); and Published (November 20, 2011). Â  Â